2019
DOI: 10.1371/journal.pone.0223928
|View full text |Cite
|
Sign up to set email alerts
|

Parental and peer support and modelling in relation to domain-specific physical activity participation in boys and girls from Germany

Abstract: BackgroundPhysical activity (PA) as a precondition of child development is related with social environmental correlates. However, domain-specific PA and gender issues have been neglected in studies on social support and modelling and PA in school-aged children. The aim of this study was to assess the relationships of parental and peer modelling and social support with domain-specific PA participation in a large sample of school-aged children, taking gender into account.Methods3,505 school children aged 6 to 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
35
1
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 74 publications
4
35
1
2
Order By: Relevance
“…The co-participation (e.g., performing physical activities together) and modelling communicative support structures may have led to increased parental social support and involvement with their daughter's engagement in the program. Studies have examined both friend and family support for PA, and results have shown that some studies have found a positive association [14,15,105,106], while others have not [16]. Results of the current study are in line with Seabra et al [107] who examined correlates of PA in schoolchildren aged 8-10 years, and found that perceived acceptance by peers in sports, and parental encouragement was positively related to PA in girls (n = 683).…”
Section: Discussionsupporting
confidence: 88%
“…The co-participation (e.g., performing physical activities together) and modelling communicative support structures may have led to increased parental social support and involvement with their daughter's engagement in the program. Studies have examined both friend and family support for PA, and results have shown that some studies have found a positive association [14,15,105,106], while others have not [16]. Results of the current study are in line with Seabra et al [107] who examined correlates of PA in schoolchildren aged 8-10 years, and found that perceived acceptance by peers in sports, and parental encouragement was positively related to PA in girls (n = 683).…”
Section: Discussionsupporting
confidence: 88%
“…Of all the individual behaviours constituting parental support, verbal and non-verbal encouragement has the greatest effect on children's PA [7] and has been positively associated with the intensity of PA in adolescents [8]. Parental support through providing transportation and equipment is also associated with increased PA in children and adolescents [9,10]. In addition, when parents co-participate in PA, their children and adolescents are more likely to meet the PA guidelines [9].…”
Section: Introductionmentioning
confidence: 99%
“…A limited number of studies have reported a positive association between peer influence and adolescents' PA [8,15,16]. Studies from the USA reported that adolescents who received peer support showed higher odds of engaging in the recommended levels of daily PA and lower odds of engaging in two or more hours of screen-time per day [8,10,14]. A 5-year longitudinal study in Scottish adolescents found that while parental support decreased with the increase of adolescents' age, peer support became more important in determining PA levels [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have suggested that parents and friends may have a role in enhancing PA [ 23 , 24 , 25 , 26 , 47 ]. Similarly, this study found that social support from family and friends (assessed separately) were significant predictors for participants meeting the PA guidelines.…”
Section: Discussionmentioning
confidence: 99%
“…Young people from NI consistently report that they value fitness, friendship and fun as being the most important part of their enjoyment and benefit from sport and PA participation [ 21 , 22 ]. A positive association between social support from parents [ 23 , 24 ] and friends [ 25 , 26 ] and PA levels has been reported. Higher levels of enjoyment have been previously associated with increased levels of PA in Irish youth [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%